Characteristics and Outcomes of Exit Sites of Buried Peritoneal Dialysis Catheters: A Cohort Study. Issue 5 (September 2018) - Keskar, Vaibhav; Biyani, Mohan; Blew, Brian; Warren, Jeff; McCormick, Brendan B.
Buried peritoneal dialysis (PD) catheters are placed months before dialysis is needed and the exit site is created when the catheter is dissected out at the initiation of dialysis. In contrast, the exit site of an unburied catheter is created by the surgeon at the time of insertion. We reviewed all patients who initiated PD at our center over a 2-year period. At each clinic visit, exit sites were subjectively classified into standard predefined groups. Outcomes of interest were the frequency of perfect exit sites at 2, 6, and 12 months and rate of exit-site infections (ESIs) at 90 days. One hundred and seventy-seven patients initiated PD during the period of interest, and 169, 157, and 144 remained on PD at 2, 6, and 12 months, respectively. Ninety-three patients had buried catheters, and 76 patients had unburied catheters. Both groups had similar frequency of perfect appearance of exit sites at 2, 6, and 12 months (37/93 vs 41/76 at 2 months; 54/87 vs 43/70 at 6 months; 50/ 81 vs 35/ 63 at 12 months in buried and unburied groups, respectively). More patients with buried catheters had ESIs in the first 3 months (7/93 vs 1/76, p = 0.059). We conclude that exit sites of buried PD catheters do not differ qualitatively from those of unburied catheters. The trend towards more ESIs with buried catheters suggests that there may be clinical consequences of the tissue trauma at time of exteriorization.